The Impact of Digitalization of Public Administration on Increasing The Efficiency and Transparency of Government Services - Erinaldi, Erinaldi; Setyarto, Dwiatmodjo Budi; Luturmas, Yulius; Sari, Regiena (Jurnal Ar Ro'is Mandalika (Armada), 2026)
The digitalization of public administration has emerged as a strategic approach to bureaucratic reform aimed at improving the efficiency and transparency of government services, particularly in developing countries such as Indonesia. This article seeks to analyze the impact of public administration digitalization on service efficiency and transparency while identifying key factors that influence its effectiveness. The study adopts a qualitative approach using library research by systematically reviewing scholarly books, peer-reviewed journal articles, and official government documents related to digital governance and public sector reform. The findings indicate that public administration digitalization positively contributes to simplifying bureaucratic procedures, accelerating service delivery, optimizing resource utilization, and enhancing information openness and accountability. However, the effectiveness of digitalization is strongly determined by institutional capacity, human resource readiness, policy coordination, organizational culture, and the availability of digital infrastructure. Overall, the study concludes that public administration digitalization can significantly enhance efficiency and transparency when implemented as a comprehensive institutional transformation rather than merely a technological initiative